A bronchogenic cyst with atrial flutter (Asian Journal of Medical Sciences, 2014)
The majority of bronchogenic cysts occur in the mediastinum and especially within the pulmonary parenchyma. Bronchogenic cysts have various clinical and radiological manifestations. In adults, these are often asymptomatic and most of them are only incidentally recognized in imaging procedures. In infancy and early childhood, compression of the tracheobronchial tree leads to symptoms and occasionaly life-threatening complications. Bronchogenic cysts have been stated rarely among the causes of an arythmia in early childhood. We reported a 7-years old female presented with paroxysmal palpitation continuing for one month. Contrast enhanced computed tomography showed cystic mass in the right hemi-thorax, compressing the right atrium. After surgical removal histopathologic examination revealed a lining of respiratory epithelium associated with a wall containing smooth muscle, a finding that is characteristic of bronchogenic cyst. DOI: http://dx.doi.org/10.3126/ajms.v5i4.9695 Asian Journal of Medical Sciences 2014 Vol.5(4); 94-96